The spy [compact disc, unabridged] : a novel - Coelho, Paulo (Random House Audio, 2016)
When Mata Hari arrived in Paris she was penniless. Soon she was feted as the most elegant woman in the city. A dancer who shocked and delighted audiences; a confidant and courtesan who bewitched the era's richest and most powerful men. But as paranoia consumed a country at war, Mata Hari's lifestyle brought her under suspicion. Until, in 1917 she was arrested in her hotel room on the Champs Elysees and accused of espionage.